A population-based study in synchronous versus metachronous metastatic esophagogastric adenocarcinoma. (March 2022) - Pape, Marieke; Vissers, Pauline A. J.; Bertwistle, David; McDonald, Laura; Slingerland, Marije; Haj Mohammad, Nadia; Beerepoot, Laurens V.; Ruurda, Jelle P.; Nieuwenhuijzen, Grard A. P.; Jeene, Paul M.; van Laarhoven, Hanneke W. M.; Verhoeven, Rob H. A.
Background: Real-world data on treatment and outcomes in patients with synchronous metastatic disease compared with patients with metachronous metastatic disease in esophagogastric cancer have not been published before. The aim of our study was to explore treatment, overall survival (OS), and time to treatment fialure (TTF) in patients with synchronous and metachronous metastatic esophagogastric adenocarcinoma. Methods: Patients with synchronous metastatic disease (2015–2017) and patients with metachronous metastatic disease initially treated with curative intent for nonmetastatic disease (2015–2016) were selected from the Netherlands Cancer Registry. OS and TTF were assessed from metastatic diagnosis for patients with synchronous, early metachronous (⩽6 months) or late metachronous (>6 months) metastatic disease using Kaplan–Meier curves with two-sided log-rank test. Results: Median OS was 4.2, 2.1, and 4.4 months in patients with synchronous, early metachronous, and late metachronous metastatic disease, respectively ( p < 0.001). The proportion of patients receiving systemic treatment was 41.3%, 21.5%, and 32.5% for synchronous, early metachronous, and late metachronous metastatic disease, respectively ( p = 0.001). Among patients receiving systemic treatment, median OS was 8.8, 4.5, and 9.1 months ( p < 0.001) and median TTF was 6.1, 3.8, and 5.7 months ( p < 0.001) in synchronous, early metachronous, and late metachronous metastatic disease, respectively. Conclusion: Patients with early metachronous metastatic disease have a worse survival compared with patients with synchronous or late metachronous metastatic disease. These patients less often receive systemic treatment, and even when treated, survival is worse compared with patients with synchronous or late metachronous metastatic disease, suggesting a more aggressive tumor behavior.